Identification of the Distribution of Asian Redtail Catfish (Hemibagrus nemurus) Based on Geographical Information Systems (GIS) in the Progo River, Magelang, Central Java - Tholibah Mujtahidah; Usman Siswanto; Sri Hidayati; Abdul Qadir Jailani (Airlangga University, 2021)
Identification of the distribution of asian redtail catfish (Hemibagrus nemurus) based on Geographical Information System (GIS) in the Progo Magelang river is a database collection process to determine the distribution patterns of H. nemurus and determine H. nemurus resources with the help of GIS and outlined in the form of a fish resource zoning map so that it can help in domestication efforts that lead to the cultivation of endemic aquatic commodities. The purpose of this study was to identify the distribution of H. nemurus, determine the status of H. nemurus resources based on diversity data to see the existing potential and to describe it in the form of a fish resource zoning map in the progo river. The research method used was a survey method with a GIS approach and the data presented in the form of descriptive analysis included fish identification and a GIS approach. GIS data processing used is in the form of hardware, namely: Personal Computer (PC), color printer and scanner, while the software in the form of software ArcGIS 9.x, Ms. Excel and Ms. Word. The method used in this study is the GIS approach with spatial analysis techniques, namely the techniques used in analyzing spatial / spatial studies. Based on the results of the study, it was shown that H. nemurus in the Progo river were found in areas with sandy clay substrates at a depth of 2 m, namely in the Ngeluwar area. The distribution of H. nemurus in the Progo river tends to be evenly distributed, because the conditions of the Progo river habitat support the life of H. nemurus.Keywords: Hemibagrus nemurus, Geographical Information System, Progo River.